Synthesis and structure–activity relationship of α-keto amides as enterovirus 71 3C protease inhibitors. Issue 7 (1st April 2016) - Zeng, Debin; Ma, Yuying; Zhang, Rui; Nie, Quandeng; Cui, Zhengjie; Wang, Yaxin; Shang, Luqing; Yin, Zheng
Graphical abstract: Abstract: α-Keto amide derivatives as enterovirus 71 (EV71) 3C protease (3C pro ) inhibitors have been synthesized and assayed for their biochemical and antiviral activities. structure–activity relationship (SAR) study indicated that small moieties were primarily tolerated at P1′ and the introduction of para -fluoro benzyl at P2 notably improved the potency of inhibitor. Inhibitors8v, 8w and8x exhibited satisfactory activity (IC50  = 1.32 ± 0.26 μM, 1.88 ± 0.35 μM and 1.52 ± 0.31 μM, respectively) and favorable CC50 values (CC50  > 100 μM). α-Keto amide may represent a good choice as a warhead for EV71 3C pro inhibitor.